Hues of Color Afterimages. (February 2020) - Koenderink, Jan; van Doorn, Andrea; Witzel, Christoph; Gegenfurtner, Karl
We studied the relationship between color afterimages and complementary colors. The hues of afterimages of 24 inducer hues, uniformly distributed over thergb color circle, were measured by an iterative method of adjustment. The judgment of equality of hue of the afterimage and a synthesized patch was effectively judged at the moment immediately after the switch-off of the inducer, when the synthesized patch went through any number of iterative adjustments. The two patches—both phenomenally present, but only one optically presented—appeared to the left and right of a fixation mark that was fixated throughout the whole procedure. Thus, both patches were present in eccentric vision. The hues of afterimages were found to be quite different from the hue of the complementary of the inducer. Almost one half of the color circle (orange to chartreuse) leads to afterimage hues in a narrow region of purples. This implies that color circles based on diametrically opposed inducer–afterimage hues are necessarily inconsistent. Yet, perhaps surprisingly, the relation between primary and afterimage hues is still approximately an involution (they are reciprocally related).